A Party without a Hangover? : On the Effects of U.S. Government Deficits - Laxton, Douglas (IMF Working Papers; Working Paper, 2007)
This paper develops a 2-country New Keynesian overlapping generations model suitable for the joint evaluation of monetary and fiscal policies. We show that a permanent increase in U.S. government deficits raises the world real interest rate and significantly increases U.S. current account deficits, especially in the medium- to long-run. A simultaneous increase in non-U.S. savings lowers the world real interest rate and further increases U.S. current account deficits. We show that conventional infinite horizon models are ill-equipped to deal with issues that involve permanent changes in public or private sector savings rates.